Towards the preparation of organic ferroelectric composites: fabrication of a gamma-glycine-bacterial cellulose composite via cold sintering process - Jitrawan Noisak; Thitirat Charoonsuk; Satana Pongampai; Nattapong Pinpru; Phakkhananan Pakawanit; Wanwilai Vittayakorn; Tosapol Maluangnont; Te‐Wei Chiu; Naratip Vittayakorn (Journal of Materials Research and Technology, 2023)
The cold sintering process (CSP) has emerged as a revolutionary technique for low-temperature processing of ceramics and composites, enabling high-density fabrication at low temperatures. In this study, we demonstrated the implementation of CSP in fabricating the γ-glycine (γ-G)-bacterial cellulose (BC) composite and evaluated the effect of sintering temperature and holding time on the microstructure and electrical properties. Our findings revealed that an increase in sintering temperature and holding time leads to grain growth, as the transient solvent (water) facilitates the closely-packed microstructure. Moreover, the addition of BC as a filler into the γ-G matrix leads to a composite with a 10% increase in hardness when BC was uniformly distributed in γ-G. The composite with a relative density of 97% was successfully obtained at 120°C/24h, preserving the γ polymorph of glycine without the unwanted transformation commonly observed with traditional sintering. We also reported the dielectric and ferroelectric properties of the γ-G-BC composite, exhibiting a remanent polarization of 0.004 μC/cm2 and a coercive field of 1.201 kV/cm. Our findings suggest that CSP is a promising approach for low-temperature processing and fabrication of ceramics, especially when incorporating structurally sensitive filler such as organic ferroelectric, to achieve high-performance composites.
Keywords: Advanced Cellulose Research Studies; Nanocomposite Films for Food Packaging; Electromagnetic wave absorption materials